Rationally Navigating Subjective Preferences in Memory Modification. - Vukov, Joseph M (Journal of Medicine & Philosophy, 2022)
Discussion of the ethics of memory modification technologies (MMTs) has often focused on questions about the limits of their permissibility. In the current paper, I focus primarily on a different issue: when (if ever) is it rational to prefer MMTs to alternative interventions? My conclusion is that these conditions are rare. The reason stems from considerations of autonomy. When compared with other interventions, MMTs do a particularly poor job at promoting the autonomy of their users. If this conclusion is true, moreover, it provides a fresh perspective on debates about the permissibility of MMTs. On the one hand, for those who would limit the use of MMTs to a narrow range of circumstances, the conclusion that MMTs are rarely preferable gives them further reason to eye MMTs with suspicion. On the other hand, for those who view MMTs as permissible in a wide range of circumstances, the conclusion may deflate their endorsement.